2020
DOI: 10.1101/2020.08.19.20178343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Coronavirus Victimization Distress and Coronavirus Racial Bias on Mental Health Among AIAN, Asian, Black, and Latinx Young Adults

Abstract: Background. People of color in the U.S. have been disproportionately impacted by the COVID 19 pandemic in terms of rates of infection and morbidity. Explanations for these disparities include over-representation as essential workers and long-standing inequities in access to health services. Prior to the pandemic, racial discrimination has been associated with depression and general anxiety. However, the effect of discrimination and racial bias specific to the Coronavirus on mental health has not been examined.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 131 publications
3
14
0
Order By: Relevance
“…Composite scale scores are computed by the sum of item responses. Internal consistency of the scale among racial/ethnic minority groups has been supported by prior research, with Cronbach's alpha ranged from 0.89 to 0.91 (16,30). The scale had good reliability for the current study, Cronbach's alpha = 0.94.…”
Section: General Anxiety Disorder Screener (Gad-7)supporting
confidence: 69%
See 4 more Smart Citations
“…Composite scale scores are computed by the sum of item responses. Internal consistency of the scale among racial/ethnic minority groups has been supported by prior research, with Cronbach's alpha ranged from 0.89 to 0.91 (16,30). The scale had good reliability for the current study, Cronbach's alpha = 0.94.…”
Section: General Anxiety Disorder Screener (Gad-7)supporting
confidence: 69%
“…Composite scale scores are computed by the sum of item responses. Prior research has shown internal consistency of the scale, with Cronbach's alpha ranged from 0.84 to 0.91 across racial/ethnic minority groups (16,29,30). The scale had good reliability for the current study, Cronbach's alpha = 0.91.…”
Section: Patient Health Questionnaire (Phq-9)mentioning
confidence: 57%
See 3 more Smart Citations